Addressing the Opioid Epidemic: Impact of Opioid Prescribing Protocol at the University of Minnesota School of Dentistry. Issue 2 (June 2018) - Nadeau, Robert; Hasstedt, Kristopher; Sunstrum, Ashley Brooke; Wagner, Chad; Tu, Harold
Prescription opioid medications continue to be abused on an epidemic level and have been shown to be a "gateway" drug to heroin abuse. Individuals experimenting with opioids commonly fall in the 10- to 19-year age range in which dentists are the highest prescribers. To reduce the number of excess opioids, the Department of Oral and Maxillofacial Surgery, University of Minnesota, developed and implemented an evidence-based opioid prescribing policy. Data were collected via electronic health record for the previous year and compared with the year following the protocol implementation. The results showed a drastic decrease (>46%) in the number of prescriptions given over a 1-year period. All departments reported a decrease in opioid prescriptions and the average number of tablets per prescription. The concern of undertreating pain was not found to be significant, as there was no increase in after-hours calls, recall appointments, or documentable emergency room visits. The results support the efficacy of an opioid prescribing policy's ability to lower the frequency and number of opioids given to patients, while still adequately treating patients' pain. Continued evaluation and modifications of the protocol and close monitoring of prescriber habits will enhance patients' pain control while also limiting the number of opioids available for abuse.